Mitigation of human factor in tomographic post processing of additive manufactured critical parts for aviation application - Stefano Benuzzi; Davide Borghi; Maria Grazia Righi; Natanaele Galavotti; Fabio Esposito (e-Journal of Nondestructive Testing)
Over the past decade, the development of the additive manufacturing process resulted in the manufacture of parts with increasingly complex geometries. The design freedom that Additive Manufacturing allows, enables the designer to develop increasingly optimized parts, capable of joining different geometries (lattice structures, thick walls, geometries optimized for heat dissipation) on a scale that can vary significantly depending on the required application. Combining such different features, however, introduces new challenges during inspection; in fact, traditional non-destructive testing suffers from significant limitations that make it not completely suitable for 100% inspection of the sample: FPI (Fluorescent Penetrant Inspection: Applicable to limited areas depending on the roughness of the surface; RT-2D (Radiographic Testing Film e Non-Film): difficulty in positioning the detector with respect to the source, need for positioning of the source-detector system in an orientation favourable to the interception of manufacturing discontinuities; UT (Ultrasonic Testing): Limitations caused by the parallelism of the area to be inspected and the surface condition of the component. Inspection by Industrial Computed Tomography (ICT), thanks to the ability to inspect the reconstructed volume using arbitrarily sliding planes (optimized according to the manufacturing strategy) combined with the complete scanning of the specimen, removes many of the limitations of traditional NDT, becoming the typically required control for inspection of components produced by Additive Manufacturing in aerospace. Simultaneously to the development of AM fabrication, tomographic systems have also adapted to meet the needs of application-dependent inspection: from micro-focus and nano-focus systems for finding micrometre-sized discontinuities, to linear accelerators for inspecting large components built in high-density alloys, the current range of machinery allows for traversing and inspecting current production by filling the gap generated by the manufacturing paradigm shift. However, it is critical to analyse the effort that is required to the technical personnel responsible for analysing tomographic data for NDT applications. In fact, unlike other inspection modes, the amount of data that must be analysed to deliberate an aviation component and the inspection methods themselves produce a high level of stress that can generate human factor phenomena, which is particularly critical for the aviation industry. The purpose of this presentation is to analyse some ways to mitigate the human factor in the post processing of tomographic data for NDT applications in the aviation industry and, ultimately, focus the attention to who is responsible for defining whether a component is fit for service or not.